Halal Tourism in Indonesia: Regional Regulation and Indonesian Ulama Council Perspective - Nurjaya; Paramarta, Vip; Dewi, R. Roro Vemmi Kesuma; Kusworo; Surasni; Rahmanita, Fika; Hidayati, Syafaatul; Sunarsi, Denok (International Journal of Criminology and Sociology, 2021)
The tourism sector is one of the sectors capable of increasing employment and economic growth. Currently, halal tourism is starting to be in great demand. This is in line with the increase in Muslim tourists from year to year. The development of halal tourism has begun to be carried out by various countries, both Muslim and non-Muslim countries. Indonesia as a multi-cultural and multi-ethnic country, of course, there are new problems that continue to surface where the law is not found either in the Quran or the Hadith, such as the emergence of the phenomenon of public demand for halal tourism in Indonesia. The purpose of this research is to describe halal tourism in Indonesia in terms of the Indonesian Council of Ulama fatwa and the government regulation. This research is a conceptual review that uses literature research methods sourced from authoritative journals, books, and documents and is still relevant to the study of halal tourism. The results showed that a large number of public requests for halal tourism visits in Indonesia in the need for normative and positive regulation regulates. the only difference is in the use of the term "sharia tourism" in the fatwa while the content in the regional regulation uses the term "halal tourism".